Pengaruh Psychological Capital dan Person-Organization Fit terhadap Subjective Well-Being Mahasiswa Pekerja (Studi Kasus pada Mahasiswa Manajemen Universitas Tadulako) - Novita Pratiwi, Selvilia; Hasanuddin, Bakri; Risnawati; Ega Nugraha, Mohammad (Universitas Muhammadiyah Pontianak, 2026)
This study examines the low subjective well-being of students who study while working due to academic and job demands. It aims to analyze the effects of Psychological Capital and Person-Organization Fit on subjective well-being among Management students of Tadulako University, class of 2022. Using a quantitative approach, saturated sampling, and multiple linear regression, data were collected from 56 respondents. The results show that Psychological Capital and Person-Organization Fit have positive and significant partial and simultaneous effects on subjective well-being. These findings imply that strengthening students’ psychological resources and organizational compatibility can improve their well-being. Keywords: Psychological Capital, Person-Organization Fit, Subjective Well-Being, Working Students, University Students, Higher Education